Dasatinib induced penile and scrotal edema a case report - Rakesh Bharti (Our Dermatology Online, 2023)
Dermatologist's opinion is often sought for various types of drug reactions/side effects-specially, if the effects are on skin, mucous membranes or genitals. Updating their knowledge about newer molecules (drugs) and their side effects,thus become a necessity. Dasatinib is a new USFD approved Tyrosine kinase inhibitor for the treatment of those Chronic Myeloid Leukemias patients who cannot tolerate Imatinib or are resistant to imatinib. Dasatinib can cause fluid retention in some patients,which can lead to peripheral edema and pleural effusion. Penile and scrotal edema are unusual manifestation of that fluid retention and very few cases have so far been reported to my knowledge of this side effect. We reporting a case of scrotal and penile edema, who had a transitory relief on stoppage of drug, restricting fluid intake and vitamin E. Recognising this side effect could have prevented many investigations and various specialist consultations and nine months of agony in my case.